(untitled) (LEARNing Landscapes, 2014)
Early career teacher attrition is a serious concern. While the problem is usually seen as one of skilling up new teachers, based on a two-year study with 50 early career teachers, we suggest the importance of attending to what sustains them. While beginning teachers need knowledge and skills, they also need places that allow them to continue to live out their stories to live by, identity stories that encompass both who they are and are becoming as teachers and as people. Attending to stories to live by means we attend to teacher knowledge, knowledge shaped in, and expressed in, both personal and professional knowledge landscapes.